Utility of proteomics in obstetric disorders: a review - Hernández-Núñez J; Valdés-Yong M (Dove Medical Press, 2015)
Jónathan Hernández-Núñez,1 Magel Valdés-Yong21Department of Obstetrics and Gynecology, Hospital Alberto Fernández-Valdés, Santa Cruz del Norte, Mayabeque, 2Department of Obstetrics and Gynecology, Hospital Luis Díaz Soto, Habana del Este, La Habana, CubaAbstract: The study of proteomics could explain many aspects of obstetric disorders. We undertook this review with the aim of assessing the utility of proteomics in the specialty of obstetrics. We searched the electronic databases of MEDLINE, EBSCOhost, BVS Bireme, and SciELO, using various search terms with the assistance of a librarian. We considered cohort studies, case-control studies, case series, and systematic review articles published until October 2014 in the English or Spanish language, and evaluated their quality and the internal validity of the evidence provided. Two reviewers extracted the data independently, then both researchers simultaneously revised the data later, to arrive at a consensus. The search retrieved 1,158 papers, of which 965 were excluded for being duplicates, not relevant, or unrelated studies. A further 86 papers were excluded for being guidelines, protocols, or case reports, along with another 64 that did not contain relevant information, leaving 43 studies for inclusion. Many of these studies showed the utility of proteomic techniques for prediction, pathophysiology, diagnosis, management, monitoring, and prognosis of pre-eclampsia, perinatal infection, premature rupture of membranes, preterm birth, intrauterine growth restriction, and ectopic pregnancy. Proteomic techniques have enormous clinical significance and constitute an invaluable weapon in the management of obstetric disorders that increase maternal and perinatal morbidity and mortality.Keywords: proteomic techniques, obstetrics, diagnosis, prediction